ANALYSIS OF LEGAL CERTAINTY AND CHALLENGES IN THE ESTABLISHMENT OF POLICY GUARANTEE INSTITUTIONS IN INDONESIA - Isdiana Syafitri; Sunarmi; Tan Kamello; Hasim Purba (Universitas Efarina, 2024)
Insurance is a financial services business that collects public funds and provides protection against losses due to an uncertain event. For supervision, the government has formed an Insurance Supervisory Agency, namely the OJK (Financial Services Authority) which functions to encourage the progress of the financial services industry and protect insurance customers. Indonesia has Law Number 40 of 2014 concerning Insurance. This study aims to provide legal protection for insurance customers in overcoming the risk of default and awaiting the formation of the Policy Guarantor Institution. Cases of unit link insurance defaults and governance violations have also occurred in several insurance companies. Such as Bakrie Insurance, Asuransji Jiwasraya, Bumiputera Insurance and Kresna Insurance. The Financial Services Authority imposes sanctions on defaulted insurance companies, including: written warnings, revoking business licenses and bankruptcy. This research is of a normative juridical nature that is qualitative descriptive. This study shows how the insurance industry in Indonesia provides protection for customer funds in resolving defaults to realize legal certainty by forming a policy guarantor program. In conclusion, although OJK imposes sanctions in cases of default, it does not appear that policyholders are protected, especially in the disbursement of claims. Therefore, a Policy Guarantor Institution needs to be formed as soon as possible to realize legal certainty.